Enlighten the Effects of Homeopathy in Management of Polycystic Ovary Syndrome: A Case Series (Advancements in Homeopathic Research, 2024)
Polycystic Ovary Syndrome (PCOS) remains a  multifaceted endocrine disorder affecting women  worldwide, necessitating effective and personalized  treatment approaches. This article presents a case  series examining the outcomes of PCOS management  through homeopathic interventions, shedding light  on the potential benefits of Homoeopathy.
Keywords: constitutional characteristics; necessitating; Staphysagria